Answer:
![- (x - 1) {}^{2} + 5](https://tex.z-dn.net/?f=%20-%20%28x%20-%201%29%20%7B%7D%5E%7B2%7D%20%20%2B%205)
Step-by-step explanation:
F(x) is a transformation from h(x).
So our starting equation is
![- (x - 1) {}^{2} - 1](https://tex.z-dn.net/?f=%20-%20%28x%20-%201%29%20%7B%7D%5E%7B2%7D%20%20-%201)
F(x) is also facing the same direction h(x) is so we dont have to reflect nothing across the x or y axis.
There isn't a vertical or horizontal stretch, compressions.
There isn't a horizontal shift as the x values stay in the same place.
There is a vertical shift. We can simply move h(x) up 6 units to get to f(x).
So our equation looks like.
![- (x - 1) {}^{2} + 5](https://tex.z-dn.net/?f=%20-%20%28x%20-%201%29%20%7B%7D%5E%7B2%7D%20%20%2B%205)
Answer:
no
Step-by-step explanation:
no,
it is not in the form
![ax {}^{2} + bx + c = 0](https://tex.z-dn.net/?f=ax%20%7B%7D%5E%7B2%7D%20%20%2B%20bx%20%2B%20c%20%3D%200)
Answer:
Joe's father is 45.
Step-by-step explanation:
3x-x+2=4
Answer:
Step-by-step explanation:
first you multiply 45 by .40 you multiply by .40 because that is the percent increase.
45*.40=18
then you just add the 18 to 45 which get you 63.
answer:40%
She has 144-100=44. 44-4=40. Medium holds to beads you will need 4 medium boxes.